Integration of substance use disorders program in general medicine education program based on Kern model - Elham Zarean; Masoomeh Moezzi; Elham Saghaei; Saeed Mardani; Fariba Fathollahi-Dehkordi (Mashhad University of Medical Sciences, 2022)
Background: Substance Use Disorders (SUD) are one of the biggest public health problems nationally and globally. It is necessary to provide specific educating programs about SUDs. The purpose of this study was to integrate some trainings which are related to substance use disorders in general medicine education.Methods: This study was a quasi-experimental and pre-test post-test intervention research. Participants were 114 students studying at different stages of medical education at Shahrekord University of Medical Sciences. The training program was designed based on the training model of David Kern. Training was integrated into pharmacology, psychology, poisoning and forensic medicine courses.  The present researchers organized a life skill workshop for third-semester medical students. The students visited an addiction treatment exhibition during community medicine externship as well. Assessment tools included questionnaires to assess knowledge, attitude, and satisfaction. Data were analyzed by SPSS 18 software.Result: In all interventions, the mean score of knowledge and knowledge self-assessment increased significantly after the intervention (p<0.001). Students' attitudes about the curriculum were favorable. Satisfaction of the majority of students about the program was high. The highest level of satisfaction was related to the internship addiction emergency program.Conclusion: The positive effect of all interventions on the perception, attitude, and satisfaction of medical students emphasized that modifying the medical educational curriculum through considering the pattern, content, and results of the interventions can be very effective in improving the performance of physicians in the field of addiction management.